Disgust sensitivity in early pregnancy as a response to high pathogen risk - Kaňková, Šárka; Takács, Lea; Hlaváčová, Jana; Calda, Pavel; Monk, Catherine; Havlíček, Jan (Frontiers in Psychology, 2023)
Introduction Considered a part of the behavioral immune system (BIS), disgust sensitivity is expected to be adjusting as a response to the actual level of the environmental health risks. Methods In this preregistered study, we tested the hypothesis that disgust sensitivity would be higher during the COVID-19 pandemic compared to the pre-pandemic period in pregnant women. In this between-subject study with a longitudinal trend design, we administered the Disgust Scale-Revised to 200 pregnant women before the pandemic and to 350 pregnant women during the pandemic. Results We found a small but significant effect of the pandemic on disgust sensitivity, such that higher disgust sensitivity was found in women pregnant during the pandemic. This effect was stronger in primiparae, however, the interaction between parity and the pandemic period was not significant. Disgust sensitivity decreased with age. No differences in terms of nausea and vomiting were found between the women pregnant before and during the pandemic. Discussion Our findings indicate that although BIS is presumed to function as a complex mechanism to prevent health-threatening behaviors, its activation in pregnant women during the COVID-19 pandemic is rather weak.